Kajian Etnomatematika Konsep Geometri dalam Corak Kain Ulos Sumatera Utara - Elvi Mailani; Johan Berkat Tubesta Lase; Meita Krisnadya Lumban Gaol; Naomi Priska Aprillia Hutapea; Nur Rarastika (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Ethnomathematics studies how mathematics interacts with culture, traditions, and customs of society. With ulos as its identity, this study will investigate one of the Indonesian tribes through its art, namely Ulos art by the Batak tribe of North Sumatra. The form of the Batak ulos variety can be associated with geometric mathematics, so that mathematics can be studied culturally in ethnomathematics studies by integrating the introduction and instillation of culture in the mathematical concepts taught. This research was collected from literature or libraries using a qualitative approach. This study aims to study the concept of geometry in the patterns of North Sumatran ulos cloth from an ethnomathematics perspective. Research shows that science and culture cannot be separated. Batak ulos is not just a traditional cloth; it is also a representation of the hierarchy of cultural values ​​maintained by the Batak people.